Myeloid-specific S100A8/A9 deficiency attenuates atrial fibrillation through prevention of TLR4/NF-kB-mediated immune cell recruitment and inflammation - Wang, Qing; Shen, Hua; Wang, Jing; Wang, Guifang; Zhang, Yufeng (Frontiers in Immunology, 2025)
BackgroundAtrial fibrillation (AF) is the most common sustained arrhythmia, frequently associated with inflammation and atrial remodeling. S100A8/A9, a calcium-binding protein complex enriched in myeloid cells, has been implicated in cardiovascular inflammation, yet its role in AF remains unexplored. This study aims to investigate the mechanistic contribution of myeloid-derived S100A8/A9 to AF pathogenesis and assess its therapeutic potential through targeted genetic deletion.MethodsTranscriptomic and single-cell RNA sequencing data from AF patients were analyzed to identify differentially expressed genes (DEGs) and immune cell signatures. S100A8/A9 emerged as top hub genes. Monocyte/macrophage-specific S100A9 conditional knockout (CKO) mice were subjected to Ach-CaCl2–induced AF, with assessments of electrophysiology, fibrosis, inflammation, and TLR4/NF-κB signaling. The functional role of this pathway was further tested using the NF-κB activator HY-18739.ResultsS100A8/A9 expression was significantly elevated in atrial tissues and myeloid cell clusters of AF patients. S100A9 CKO mice exhibited reduced AF inducibility and duration, accompanied by attenuation of atrial fibrosis, inflammatory cytokine production, and monocyte infiltration. Mechanistically, S100A9 deletion suppressed activation of the TLR4/IRAK1/TRAF6/NF-κB pathway. These effects were reversed by pharmacologic NF-κB reactivation with HY-18739, confirming the centrality of this pathway.ConclusionMyeloid-derived S100A8/A9 amplifies AF by promoting monocyte recruitment and inflammation via the TLR4/NF-κB axis. Targeting this pathway may offer a promising therapeutic strategy for AF prevention and treatment.